Lung Ultrasound Diagnostic Accuracy in Neonatal Pneumothorax. (3rd May 2016) - Cattarossi, Luigi; Copetti, Roberto; Brusa, Giacomo; Pintaldi, Stefano
Abstract : Background . Pneumothorax (PTX) still remains a common cause of morbidity in critically ill and ventilated neonates. At the present time, lung ultrasound (LUS) is not included in the diagnostic work-up of PTX in newborns despite of excellent evidence of reliability in adults. The aim of this study was to compare LUS, chest X-ray (CXR), and chest transillumination (CTR) for PTX diagnosis in a group of neonates in which the presence of air in the pleural space was confirmed. Methods . In a 36-month period, 49 neonates with respiratory distress were enrolled in the study. Twenty-three had PTX requiring aspiration or chest drainage (birth weight 2120 ± 1640 grams; gestational age = 36 ± 5 weeks), and 26 were suffering from respiratory distress without PTX (birth weight 2120 ± 1640 grams; gestational age = 34 ± 5 weeks). Both groups had done LUS, CTR, and CXR. Results . LUS was consistent with PTX in all 23 patients requiring chest aspiration. In this group, CXR did not detect PTX in one patient while CTR did not detect it in 3 patients. Sensitivity and specificity in diagnosing PTX were therefore 1 for LUS, 0.96 and 1 for CXR, and 0.87 and 0.96 for CTR. Conclusions . Our results confirm that also in newborns LUS is at least as accurate as CXR in the diagnosis of PTX while CTR has a lower accuracy.